Efektivitas Kombinasi Meditasi Dzikir Dan Konsumsi Teh Rosella Dalam Menurunkan Tekanan Darah Pada Pasien Hipertensi - Putri Arinda Nuraningrum; Marsaid Marsaid; Joko Wiyono; Wiwin Martiningsih (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Hypertension remains a significant public health concern and is one of the primary risk factors contributing to cardiovascular morbidity and mortality. Besides pharmacological management, the implementation of non-pharmacological approaches, including relaxation-based techniques and herbal interventions, is important in supporting optimal blood pressure regulation. Dzikir meditation and roselle tea are complementary therapies known for their potential calming and blood pressure lowering properties; however, evidence regarding the effectiveness of their combined application is still limited. Objective: To identify the effectiveness of a combination of dzikir meditation and roselle tea consumption on reducing blood pressure in patients with hypertension in RW 2, Temas Subdistrict, Batu City. Methods: This article was derived from a quasi-experimental study with a pretest–posttest control group design involving 40 hypertensive patients selected by purposive sampling and divided into an intervention group (n = 20) and a control group (n = 20). The intervention group received dzikir meditation and roselle tea, while the control group received standard pharmacological therapy. Blood pressure was measured before and after the intervention and analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test. Results: The results showed a significant reduction in systolic and diastolic blood pressure in the intervention group after the intervention (p < 0.05). In contrast, the control group did not show a significant change in blood pressure (p > 0.05). Furthermore, there was a significant difference in blood pressure reduction between the intervention and control groups for both systolic and diastolic pressure (p < 0.05). Conclusion: The combination of dzikir meditation and roselle tea consumption is effective in reducing blood pressure in patients with hypertension and can be considered as a complementary therapy alongside pharmacological treatment.